Time-preference heterogeneity and multiplicity of equilibria in two-group bargaining - Daniel Cardona; Antoni Rubí-Barceló (Games, 2016)
We consider a multilateral bargaining game in which the agents can be classified into two groups according to their instantaneous preferences. In one of these groups there is one agent with a different discount factor. We analyze how this time-preference heterogeneity may generate multiplicity of equilibria. When such an agent is sufficiently more patient than the rest, there is an equilibrium in which her group-mates make the same proposal as the members of the other group. Thus, in heterogeneous groups the presence of more patient members may reduce the utility of its members.
Keywords: C78; 330; multilateral bargaining; one-dimensional; multiple equilibria; time preference